Effect of Learning Platforms on Students’ Retention of Algebra Concepts in Port Harcourt in Metropolis, Rivers State (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: This research aimed to investigate the effect of Gamified Quizizz and Google Classroom Platforms on students' retention in algebra. Three research questions and three hypotheses guided the study. A quasi-experimental design was employed, involving 251 Junior Secondary School III Mathematics students (JSS III) from intact classes in three selected private junior secondary schools in the Port Harcourt Metropolis. Data were collected using the Algebra Performance Test (APT), which was further turned Algebra Retention Test (ART), which was validated by three experts and had a reliability coefficient 0.92. Data analysis was performed using SPSS software, with a significance level set at 0.05. Data were analysed using mean, standard deviation, and analysis of covariance (ANCOVA) at the 0.05 significance level. Findings revealed that the retention level of the students taught Algebra concepts using GQP was higher than students taught Algebra concepts using GCP, followed by students taught Algebra concepts using FFM. Also, findings showed that the joint effect of GQP, GCP and FFM and gender in students’ retention of the knowledge of Algebra concepts. The study concluded that gamified learning platforms, particularly Quizizz (GQP), significantly improve Algebra retention compared to Google Classroom (GCP) and traditional face-to-face (FFM) methods. It was, however, recommended that curriculum planners should integrate gamified learning approaches into the educational framework for secondary schools in Rivers State to improve the retention of mathematical concepts among students.